Sensing characteristics of a grating-based fabry-perot structure in a biconical tapered fiber - Madan, Aayush (2022)
In this article, we present the sensing charac-teristics of a fiber Bragg grating (FBG) based Fabry-Perot (FP) structure in an acrylate coated biconical tapered fiber. The fiber-diameter was tapered down to 70μm using flame brushing technique followed by point-by-point writing of the FP structure within the fiber core using infrared femtosecond laser pulse irradiation. The sensing structure consists of two identical gratings separated by a small gap. The strain characteristics, ranging up to 3440μϵ, and the temperature characteristics, ranging up to 225 °C, have been investigated. The sensing sensitivities for strain and temperature were found out to be 2.32 pm/μϵ and 8.86 pm/°C, respectively.